2020
DOI: 10.1175/jcli-d-19-0321.1
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and Tracking Coastal Precipitation in the Tropics: Methods and Insights into Multiscale Variability of Tropical Precipitation

Abstract: Abstract We propose an algorithm to detect and track coastal precipitation systems and we apply it to 18 years of the high-resolution (8 km and 30 min) Climate Prediction Center CMORPH precipitation estimates in the tropics. Coastal precipitation in the Maritime Continent and Central America contributes to up to 80% of the total rainfall. It also contributes strongly to the diurnal cycle over land with the largest contribution from systems lasting between 6 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Previous studies have shown the importance of MCS lifetime on contribution to rainfall (e.g., Coppin et al ., 2020; Feng et al ., 2021; Roca et al ., 2014). Roca et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown the importance of MCS lifetime on contribution to rainfall (e.g., Coppin et al ., 2020; Feng et al ., 2021; Roca et al ., 2014). Roca et al .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown the importance of MCS lifetime on contribution to rainfall (e.g., Coppin et al, 2020;Feng et al, 2021;Roca et al, 2014) also suggested propagation distance has an impact on rainfall contribution, with MCSs propagating more than 250 km having the largest contribution. Also, fast-moving storms cause more problems for meteorological agencies, in that they can arrive at a location quickly without much warning; so, understanding these systems is important.…”
Section: Locations and Properties Of Different Types Of Mcssmentioning
confidence: 96%
See 1 more Smart Citation